Self-Regulated Learning on Academic Stress of Students Working on Their Thesis - Nasruddin, Dedi; Lena Nessyana Pandjaitan (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Final-year students have a lot of academic burdens, so it is easier to trigger academic stress. Strategies can be given to reduce academic stress, namely self-regulated learning. The study aims to measure the effectiveness of self-regulated learning training on academic stress for students working on their thesis. The quantitative research approach uses a randomized pretest-posttest control group experimental design. Data collection uses the academic stress scale. Data management is a difference test and an effect size test. The 10 research participants were divided into two groups, namely, 5 participants in the experimental group and 5 participants in the control group. The study's results showed that students' academic stress decreased after being given self-regulated learning training. A comparison of the two groups of participants, namely the experimental group, showed that they experienced a decrease in academic stress while the control group did not experience any changes in academic stress. The difference test and effect size results showed changes and significant influences in the experimental group after being given self-regulated learning training. Based on the follow-up results, it was stated that self-regulated learning training can be applied to academic problems, including academic stress.